Reproductive characteristics modify the association between global DNA methylation and breast cancer risk in a population-based sample of women. - Lindsay J Collin; Lauren E McCullough; Kathleen Conway; Alexandra J White; Xinran Xu; Yoon Hee Cho; Sumitra Shantakumar; Susan L Teitelbaum; Alfred I Neugut; Regina M Santella; Jia Chen; Marilie D Gammon (PLoS ONE, 2019)
DNA methylation has been implicated in breast cancer aetiology, but little is known about whether reproductive history and DNA methylation interact to influence carcinogenesis. This study examined modification of the association between global DNA methylation and breast cancer risk by reproductive characteristics. A population-based case-control study assessed reproductive history in an interviewer-administered questionnaire. Global DNA methylation was measured from white blood cell DNA using luminometric methylation assay (LUMA) and pyrosequencing assay (long interspersed elements-1 (LINE-1). We estimated adjusted odds ratios (ORs) and 95% confidence intervals (CIs) among 1 070 breast cancer cases and 1 110 population-based controls. Effect modification was assessed on additive and multiplicative scales. LUMA methylation was associated with elevated breast cancer risk across all strata (comparing the highest to the lowest quartile), but estimates were higher among women with age at menarche ≤12 years (OR = 2.87, 95%CI = 1.96-4.21) compared to >12 years (OR = 1.66, 95%CI = 1.20-2.29). We observed a 2-fold increase in the LUMA methylation-breast cancer association among women with age at first birth >23 years (OR = 2.62, 95%CI = 1.90-3.62) versus ≤23 years (OR = 1.32, 95% CI = 0.84-2.05). No modification was evident for parity or lactation. Age at menarche and age at first birth may be modifiers of the association between global DNA methylation and breast cancer risk.